2015
DOI: 10.1063/1.4934812
|View full text |Cite
|
Sign up to set email alerts
|

Improving the counting efficiency in time-correlated single photon counting experiments by dead-time optimization

Abstract: Time-Correlated Single Photon Counting (TCSPC) has been long recognized as the most sensitive method for fluorescence lifetime measurements, but often requiring "long" data acquisition times. This drawback is related to the limited counting capability of the TCSPC technique, due to pile-up and counting loss effects. In recent years, multi-module TCSPC systems have been introduced to overcome this issue. Splitting the light into several detectors connected to independent TCSPC modules proportionally increases t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…In order to gather measurements done with different channels (SPAD + TAC), a calibration procedure is mandatory to compensate for mismatches, i.e., offsets and mean bin widths of the TCSPC chains are slightly different. We employed an offline calibration, done by software on the recorded events, based on the algorithm proposed by Peronio et al 15 We tested the validity of the calibration procedure by acquiring the instrument response function (IRF) of the system for all the 32 detectors. The laser source integrated in the SP8-X is a supercontinuum laser by NKT that was tuned at 488 nm with a repetition rate of 40 MHz and the full-scale range of the TACs was set to 25 ns accordingly.…”
Section: Resultsmentioning
confidence: 99%
“…In order to gather measurements done with different channels (SPAD + TAC), a calibration procedure is mandatory to compensate for mismatches, i.e., offsets and mean bin widths of the TCSPC chains are slightly different. We employed an offline calibration, done by software on the recorded events, based on the algorithm proposed by Peronio et al 15 We tested the validity of the calibration procedure by acquiring the instrument response function (IRF) of the system for all the 32 detectors. The laser source integrated in the SP8-X is a supercontinuum laser by NKT that was tuned at 488 nm with a repetition rate of 40 MHz and the full-scale range of the TACs was set to 25 ns accordingly.…”
Section: Resultsmentioning
confidence: 99%
“…Concerning the conversion electronics, recent advances in time-measurement circuits allowed us to decrease the dead time associated to the electronics down to about 10 nanoseconds [10][11][12]. For instance, we recently proposed a converter based on an array of Time-to-Amplitude Converters (TACs), which is able to measure more than an event during each excitation cycle, given an average detection rate up to 80 MHz [13]. In addition, it features excellent performance in terms of timing jitter (as low as 20 ps FWHM) and Differential Non Linearity (better than 0.04 LSB peak-peak) [14].…”
Section: Dead Time and Measurement Speed In Tcspc Systemsmentioning
confidence: 99%
“…Nevertheless, we recently demonstrated that the combination of an array of TAC converters and a sequential router can reduce to a negligible value the dead time associated to the electronics. 20 This architecture, known as Fast TAC (F-TAC), can lead to a significant simplification of the routing logic tasks since the converters can operate at the same rate of the laser.…”
Section: System Architecturementioning
confidence: 99%